2013
DOI: 10.1074/jbc.m113.484683
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Localization and Characterization of Cytosolic Binding Partners for Gla Domain-containing Proteins PRRG4 and PRRG2

Abstract: Background: PRRG proteins were cloned more than a decade ago, but their function is still not known.Results: Several novel protein-protein interactions for PRRG are identified by array screening and pulldown analysis.Conclusion: PRRG-initiated signaling events most likely depend on proteins with WW domains.Significance: The protein-protein interactions identified here may help to elucidate the roles of PRRG proteins in different physiological settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Vitamin K acts as a cofactor to γ-glutamyl carboxylase (GGCX), an enzyme that catalyzes glutamic acid residues of specific proteins to γ-carboxyglutamic acid (Gla) to form Gla-containing proteins. These proteins, also called vitamin K-dependent proteins (VKDPs) [1][2][3][4][5][6][7][8][9][10][11], are listed in Table 1. When intake of vitamin K is insufficient, VKDPs are not fully activated and fail to execute their specific functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin K acts as a cofactor to γ-glutamyl carboxylase (GGCX), an enzyme that catalyzes glutamic acid residues of specific proteins to γ-carboxyglutamic acid (Gla) to form Gla-containing proteins. These proteins, also called vitamin K-dependent proteins (VKDPs) [1][2][3][4][5][6][7][8][9][10][11], are listed in Table 1. When intake of vitamin K is insufficient, VKDPs are not fully activated and fail to execute their specific functions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, vitamin K is expected to have various health benefits [13], preventing or alleviating cardiovascular disease, bone fracture, diabetes mellitus, cancer, liver disease, chronic kidney disease, immune disorder, neurological disease, and obesity. γ-carboxyglutamic acid-rich protein Inhibition of ectopic calcification, anti-inflammatory [5] Periostin Inhibition of ectopic calcification, tissue regeneration [6] Growth arrest-specific protein 6 Cell proliferation [7,8] Proline-rich γ-carboxy glutamyl proteins 1 and 2 Not well-known [9,10] γ-glutamyl carboxylase γ-glutamyl carboxylation of vitamin K-dependent proteins [11] Recently, vitamin K2 (MK-7) has been found to be highly effective in activating extrahepatic VKDPs at nutritional doses. In this study, we review the properties of MK-7.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to containing PDZ domains, the Magi family of scaffold proteins is unique among all other PDZ scaffolding proteins because it also contains WW domains (21). Sequence alignment demonstrated that Magi-1 WW domains are highly homologous to neural precursor cell expressed developmentally down-regulated protein 4-2 (Nedd4-2) WW domains (22), and the WW domains of Magi-1 have an absolute requirement for a PPXY motif for protein interaction compared with other WW domaincontaining proteins (23). Although there are many PDZ binding proteins known to associate with Magi-1, it remains unclear as to why Magi-1 contains WW domains.…”
mentioning
confidence: 99%
“…The vertebrate proline rich and Gla domain genes PRRG1-4, also known as PRGP1, PRGP2, TMG3 and TMG4 respectively [ 16 , 17 ], encode short transmembrane proteins. PRRG4 protein has been found in the Golgi apparatus and at the cell surface [ 18 20 ]. All PRRG proteins contain a Gla domain in which glutamic acid (Glu) residues are γ-carboxylated in the endoplasmic reticulum by γ-glutamyl carboxylase (GGCX) [ 21 , 22 ] to form γ-carboxyglutamate (Gla) residues.…”
Section: Introductionmentioning
confidence: 99%
“…The PY motifs of Comm1 interact with the WW domain of the Nedd4 E3 ubiquitin-protein ligase [ 9 ]. The PY motifs of the human PRRG4 protein also interact with the WW domain of Nedd4 [ 18 ]. The interaction with Nedd4 is only implicated in endocytosis of Robo from the cell surface and not in regulation of Robo exocytosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%